2013
DOI: 10.5455/2319-2003.ijbcp20130308
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of amlodipine and cilnidipine on blood pressure, heart rate, proteinuria and lipid profile in hypertensive patients

Abstract: Background: Hypertension is a widespread public health problem and a major risk factor. Amlodipine, a calcium channel blocker is frequently used in the treatment of hypertension. Since Amlodipine primarily L-type calcium channel blocker (CCB) and thus reduces blood pressure, it stimulates sympathetic nerve activity leading to reflex increase in heart rate. Cilnidipine, a new type of CCB which can inhibit L- type calcium channels but also N-type calcium channels. We compare the clinical effectiveness of Amlodip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
5
10
1
1
Order By: Relevance
“…Also, a significant decrease in heart rate with cilnidipine therapy has been observed in hypertensive patients with CKD on treatment with an RAS inhibitor in a study done by Hatta T et al 32 Our study also showed a significant difference in the change in mean heart rate from baseline at 6 weeks and 12 weeks between the amlodipine and cilnidipine groups. These results correlate well with the observations made in studies done by Zaman et al, 18 Kaur M et al 28 and Hoshide S et al 29 Elevated heart rate is associated with higher risk of allcause mortality and cardiovascular events. Ischaemic events, stroke, heart failure and renal failure are the consequences of ignoring sympathetic overactivity in patients with high blood pressure according to 30.91%, 25.39%, 20.97% and 22.30% physicians respectively according to a study done by Dalvi K et al 33 A significant decrease in heart rate with cilnidipine therapy can be attributed to its dual L/N-type calcium channel blocking property.…”
Section: Effect On Heart Ratesupporting
confidence: 91%
See 1 more Smart Citation
“…Also, a significant decrease in heart rate with cilnidipine therapy has been observed in hypertensive patients with CKD on treatment with an RAS inhibitor in a study done by Hatta T et al 32 Our study also showed a significant difference in the change in mean heart rate from baseline at 6 weeks and 12 weeks between the amlodipine and cilnidipine groups. These results correlate well with the observations made in studies done by Zaman et al, 18 Kaur M et al 28 and Hoshide S et al 29 Elevated heart rate is associated with higher risk of allcause mortality and cardiovascular events. Ischaemic events, stroke, heart failure and renal failure are the consequences of ignoring sympathetic overactivity in patients with high blood pressure according to 30.91%, 25.39%, 20.97% and 22.30% physicians respectively according to a study done by Dalvi K et al 33 A significant decrease in heart rate with cilnidipine therapy can be attributed to its dual L/N-type calcium channel blocking property.…”
Section: Effect On Heart Ratesupporting
confidence: 91%
“…The antihypertensive effect of cilnidipine has been demonstrated in hypertensive patients and also in patients with severe hypertension or with complications such as chronic kidney disease, cerebrovascular disease and diabetes. In individuals with diabetes, Cilnidipine also improves lipid profile 18 and insulin resistance. 19 N-type Ca 2+ channels are localised at the nerve endings in the sympathetic and central nervous systems, which regulate the release of neurotransmitters.…”
mentioning
confidence: 99%
“…12 While, at 24 weeks both SBP and DBP fall is more in this study as compared to Zaman ZA, et al (14 mm Hg (8.43%) and 8 mm Hg (8.16%) in patients of hypertension with or without T2DM at 24 weeks). 13 In comparison to Agodoa LY, et al both SBP and DBP fall is less at 12 weeks (6.02 mmHg and 8.07 mmHg) while more fall is seen in both these BP at 24 weeks (20.76 mmHg and 10 mmHg respectively at 12 and 24 weeks) in this study.…”
Section: Group Amentioning
confidence: 50%
“…15 Increase in urinary albumin (by 59.87%) at 24 weeks, is more or less as reported by Agodoa LY et al (58% for urinary protein)14 but more than as disclosed by KOJIMA S et al (30.12%) and Zaman ZA et al (16.67%, urinary protein/creatinine ratio) (both studies was conducted on patients of hypertension with or without T2DM). [13][14][15] Fall in value of eGFR at 12 weeks and 24 weeks was observed.…”
Section: -15mentioning
confidence: 94%
“…A unique 4 th generation 1, 4 dihydropyridine derivative calcium channel blocker Cilnidipine, that inhibits multiple calcium channels have been developed over the past decade. Cilnidipine acts significantly both on N-type calcium channels located on peripheral sympathetic nerve fibres and L-type calcium channels located on vasculature is approved for therapy of essential hypertension [25].…”
Section: Introductionmentioning
confidence: 99%